2021
DOI: 10.4236/msce.2021.93002
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characterisation for Potential Uses as Industrial Mineral of Bauxite from Débélé, Guinea

Abstract: Assessing the potential uses as industrial mineral, bauxite from Débélé, Guinea, has been characterised by chemical and mineralogical analyses, the determination of the amorphous content, the rate of portlandite consumption in an aqueous solution, the strength activity index, and the thermal behaviour up to 1200˚C. It was evidenced that the raw sample is gibbsite-rich type bauxite with about 45.06 wt% of alumina, 23.80 wt% of iron oxide, and 1.74 wt% of silica. It meets the chemical composition required for ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…The bands appearing at 3619, 3524, 3441, and 3366 cm −1 in the spectra of bauxite represent the stretching frequencies of the hydroxyl group (O–H bonds), which correspond to the mineral of gibbsite as has been observed on XRD of bauxite (Figure 4). 36–38 Those located at around 1014 and 966 cm −1 are attributed to asymmetric Si–O–Si (Al) vibrations from single tetrahedral SiO 4 and AlO 4 . The bands centered at 738 and 668 cm −1 are linked to the vibrations mode of the O–H (Al (VI) –OH) bonds of the hydroxyl group of gibbsite 39 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bands appearing at 3619, 3524, 3441, and 3366 cm −1 in the spectra of bauxite represent the stretching frequencies of the hydroxyl group (O–H bonds), which correspond to the mineral of gibbsite as has been observed on XRD of bauxite (Figure 4). 36–38 Those located at around 1014 and 966 cm −1 are attributed to asymmetric Si–O–Si (Al) vibrations from single tetrahedral SiO 4 and AlO 4 . The bands centered at 738 and 668 cm −1 are linked to the vibrations mode of the O–H (Al (VI) –OH) bonds of the hydroxyl group of gibbsite 39 .…”
Section: Resultsmentioning
confidence: 99%
“…The bands appearing at 3619, 3524, 3441, and 3366 cm −1 in the spectra of bauxite represent the stretching frequencies of the hydroxyl group (O-H bonds), which correspond to the mineral of gibbsite as has been observed on XRD of bauxite (Figure 4). [36][37][38] Those located at around 1014 and 966 cm −1 F I G U R E 5 FT-IR spectrum of selected raw materials.…”
Section: Characterization Of Raw Materialsmentioning
confidence: 99%
“…Four (4) main sources of literature information thought to be representative of the wider deposit were used for the Bauxite deposits; two (2) different locations on the Balaya plateau (herein labelled as Balaya Plateau-1 and Balaya plateau-2), all at Debele in the Kindia region of the country and then one (1) on the largest deposit at Sangaredi plateau. Detailed outcome of those investigations can be found elsewhere [ 1 , 21 , 38 , 42 ]. Mineralogical constituents and geochemical compositions have been culled and reorganized as shown in Table 5 , Table 6…”
Section: Methodsmentioning
confidence: 99%
“…It was observed that no two samples possess the same characteristics even though dug from the same area from the data of the investigators. This differences in mineralogical compositions are not surprising because they are known to be dependent on the geographical location and depth of the ore from which they were obtained [ 42 , 43 ]. Since high quality bauxite deposits are becoming scarce, it has become necessary for extensive comparative analysis of the mineralogical and chemical composition of deposits; which are available in relatively large quantities that would be profitable for alumina production to be identified and brought to the fore.…”
Section: Geology Of African Bauxite Orementioning
confidence: 99%
“…Bauxite from Débélé, Kindia (Guinea) with the chemical and mineralogical characteristics presented in Table I [20], was dried at room temperature, crushed, and sieved with a 75 µm mesh to obtain a powder with a red colour corresponding to 2.5YR4/8, according to the Munsell code [21]. This powder was considered as a mineral additive and denoted as RB, it was then calcined at 600 °C in a muffle furnace with a heating rate of 5 °C/min to obtain another sample of mineral additive denoted as CB.…”
Section: A Materials Samplingmentioning
confidence: 99%